The therapeutic value of treatment for multiple sclerosis: analysis of health technology assessments of three European countries - Gozzo, Lucia; Romano, Giovanni Luca; Brancati, Serena; Longo, Laura; Vitale, Daniela Cristina; Drago, Filippo (Frontiers in Pharmacology, 2023)
In accordance with European regulation, medicines containing a new active substance to treat neurodegenerative diseases as well as autoimmune and other immune dysfunctions must be approved by the European Medicines Agency (EMA) through the centralized procedure before they can be marketed. However, after EMA approval, each country is responsible for national market access, following the assessment performed by health technology assessment (HTA) bodies with regard to the therapeutic value. This study aims to provide a comparative analysis of HTA recommendations issued by three EU countries (France, Germany, and Italy) for new drugs for multiple sclerosis (MS) following EMA approval. In the reference period, we identified 11 medicines authorized in Europe for MS, including relapsing forms of MS (RMS; n = 4), relapsing–remitting MS (RRMS; n = 6), secondary progressive MS (SPMS; n = 1), and the primary progressive form (PPMS; n = 1). We found no agreement on the therapeutic value (in particular, the “added value” compared to the standard of care) of the selected drugs. Most evaluations resulted in the lowest score (“additional benefit not proven/no clinical improvement”), underlining the need for new molecules with better efficacy and safety profiles for MS, especially for some forms and clinical settings.